Exploring water and ion transport process at silicone/copper interfaces using in-situ electrochemical and Kelvin probe approaches. (20th February 2021) - Munirathinam, B.; van Dam, J.P.B.; Herrmann, A.; van Driel, W.D.; De Buyl, F.; Erich, S.J.F.; van der Ven, L.G.J.; Adan, O.C.G.; Mol, J.M.C.
Abstract: In general, packaging materials which encapsulate light emitting diodes (LEDs) and microelectronic devices offer barrier protection against several environmental hazards such as water and ionic contaminants. However, these encapsulants may provide pathways for water and ionic contaminants to reach the metal/polymer interfaces and provoke local corrosion of electronics, which is a major reliability concern for polymer encapsulated LEDs and microelectronics. As the water and corrosive constituents play a crucial role in their reliability, water uptake kinetics, interfacial ion transport and delamination behaviour of silicone coated copper model system, mimicking a typical microelectronics packaging system, is explored in the present work. Electrochemical impedance spectroscopy (EIS) integrated with attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy studies revealed that water diffusion inside the silicone network is Fickian in nature and the evolution of the observed time constants are related to the diffusion and interfacial reactions. A decrease of impedance magnitude with time was observed in EIS measurements concurrently with water absorption bands shifting towards lower wavenumber in ATR-FTIR measurements, implying the growth of strong hydrogen bonding between water molecules and the silicone network. The estimated diffusion constant of water using the capacitance method was in the order of 7 × 10 -12  m 2 s −1 and the water absorption volume fraction was in the range of 0% to 0.30%. Scanning Kelvin probe studies elucidated the ion transport process occurring at the silicone/copper interface in a humid atmosphere. The interfacial ion transport process is controlled by the interfacial electrochemical reactions at the cathodic delamination front and the estimated average delamination rate is 0.43 mm h -1/2 . This work demonstrates that exploring ion and water transport in the silicone coating and along the silicone/copper interface is of pivotal importance as part of a detailed reliability assessment of the polymer encapsulated LEDs and microelectronics.